Nutrition in Ivory Coast - Diatta, Ampa Dogui; Casu, Laura; Dramé, Mariame; Uzhova, Irina; Kaboré, Judith; Touré, Fanta; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
This brief summarizes nutrition-relevant policies in Ivory Coast. We examine i) nutrition context, objectives, indicators, budget, and activities, ii) key beneficiaries, actors, and coordination, iii) monitoring, evaluation, and accountability, and iv) whether current policies are aligned with the World Health Assembly (WHA) global targets.